A Curly Q: Is Frizz a Matter of Friction?. (August 2021) - Skedung, Lisa; Collier, Elizabeth S.; Harris, Kathryn L.; Rutland, Mark W.; Applebaum, Mara; Greaves, Andrew J.; Luengo, Gustavo S.
The oft discussed and fretted over environmental influences on hair have led to a popular consensus which suggests that elevated temperature and humidity lead to frizzier, wilder hair. However, few attempts at actually quantifying these effects have been made. Although frizziness is usually perceived visually, here the influence of variations in temperature and humidity on the tactile perception and friction of curly and straight hair were investigated. It is shown that changes in humidity may disproportionately affect perceived frizziness of curly hair by touch due to concurrent changes in the tactile friction.